Lewis acid catalyzed annulation of spirocyclic donor–acceptor cyclopropanes with exo-heterocyclic olefins: access to highly functionalized bis-spirocyclopentane oxindole frameworks. Issue 49 (31st May 2019) - Singh, Kuldeep; Pramanik, Sourav; Hamlin, Trevor A.; Mondal, Biplab; Das, Dinabandhu; Saha, Jaideep
Abstract : Oxindole-activated spiro-DAC is used as synthon to prepare complex bis-spirocyclopentane oxindole frameworks via ring-enlargement. Abstract : Lewis acid catalyzed highly efficient [3+2] annulation of spirocyclic Donor–Acceptor cyclopropanes (DACs) with exo -heterocyclic olefins is reported to furnish various biologically relevant dispiro-2, 3-dioxopyrrolidine[cyclopentane]oxindole and dispiropyrazolone[cyclopentane]oxindole frameworks. This report highlights the use of oxindole-activated spiro-DACs as potential synthons to access complex dispirocarbocyclic oxindoles via ring-enlargement of the former, with high yields and diastereoselectivity.